MARRIAGE OF THE MIGHT: ARTICULATING THE INDIAN CONDITIONING TOWARDS MARRIAGE THROUGH ISMAT CHUGHTAI’S SHAHUHAR KE KHATIR’ AND ‘CHAUTHI KA JODA’ (Proceedings of the World Conference on Women’s Studies, 2023)
The Indian Society has existed for centuries as a socio-sexually patriarchal society where marriage features as one of the major facets of building of the family structure. What functions as the aside to this exchange, is the perpetual subjugation of women in the pretext of providing them a ‘respectable’ social status. This Paper would take into consideration two stories written by Ismat Chughtai, Shahuhar ke Khatir’ and ‘Chauthi ka Joda’ that serve as a stark commentary on the ritual of marriage in India by exposing the multi-layered sexual discrimination, torture and oppression that comes along with it.  As the subcontinent's one of the famous feminist writers, Chughtai (1915-1991) wrote with panache and depicted the tyrannies of contemporary society. Through this paper, I intend to raise questions on the Indian tradition of marriage and the sexual commercialization behind it. The stories throw light upon the duplicity of the society and how women are subjected to constant ostracization for failing to match to the standards of the society. By taking into light various ancient Indian cultural treatises on sexuality and marriage, it would like to position the stories and the method in which they develop to discuss marriage as an emblem of the culture of the society.
Keywords: Sexual Commercialization; Duplicity; Procreation; Heteronormativity